BUREAUCRATIC GOVERNANCE EFFECTIVENESS IN IMPLEMENTATION FAMILY HOPE PROGRAM (PKH) IN PALOPO CITY - Didik Iskandar; Ramlawati Jabbar (Al Qisthi Jurnal Sosial dan Politik, 2021)
Effectiveness of bureaucratic governance is defined as extent to which the bureaucratic organization realizes the program goals that have been planned and determined. Family Hope Program is a conditional cash transfer program for underprivileged communities that prioritizes three main components, namely health, education and social welfare. This study is aimed at assessing the effectiveness of bureaucratic governance in the implementation of the family of hope program in Palopo City. The research method used descriptive qualitative with data collection techniques, conducting interviews, documentation, and direct observation at location. Data management techniques used data reduction, data display, and drawing conclusions. Palopo City is the location of this research. From the results of the study, it is known that the implementation of the family of hope program in Palopo City has not been entirely effective based on effectiveness measures used, including production, efficiency, satisfaction, adaptation, and development. So that bureaucratic governance activities as the responsible organization have not been effective in implementing the family of hope program in Palopo City.